TAYYOR MAHSULOT TANNARXI. MAHSULOTNI SOTISH TANNARXI (SOTILGAN MAHSULOT TANNARXI) - Xudaynazarova Dilnoza,; Jalilov Shohjahon, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines the economic essence of the cost of finished goods and the cost  of  goods  sold  (COGS),  as  well  as  their  formation  process  and  impact  on  the financial performance of enterprises. The study analyzes the structure of production costs, methods of cost accounting, and modern approaches to determining product cost. In  addition,  the  direct  influence  of  the  cost  of  goods  sold  on  revenue  and  profit indicators is substantiated. The  paper  highlights  the  differences  and  interrelations  between  the  cost  of finished goods and the cost of goods sold, emphasizing their importance in evaluating enterprise efficiency. Based on practical examples, opportunities for cost reduction and cost optimization are explored. The findings of the research contribute to improving cost  management  practices,  enhancing  competitiveness,  and  ensuring  financial stability in enterprises.